Religious Moderation Education Strategy at the Mualaf Assembly - Kader, Muhammad Rizqi; Rofiq, Muhammad Husnur; Ma`arif, Muhammad Anas (At-tadzkir: Islamic Education Journal, 2024)
This article describes the religious moderation education strategy and its implications at the Manado branch of the North Sulawesi Converts Association. The research that has been used is qualitative research with a phenomenological approach. The data collection techniques in this research are through observation, interview, and documentation. The important finding of this article is that the strategy of Religious Moderation Education at the North Sulawesi Converts Assembly Manado City Branch departs from the discussion of research results and the theory of David Hunger and Thomas L Whelen, which has several stages in strategy: the first stage, Strategy Formulation, the second stage, Strategy Implementation, Strategy, and the third stage, Strategy Evaluation. The Implication of the Religious Moderation Education Strategy at the North Sulawesi Mualaf Council Manado City Branch is based on the discussion of research results and the theory of Fethullah Gulen, which has several stages in Moderation Education: the first stage, Golden Generation, the second stage, Love and Tolerance, and the third stage, Islam Rahmatan Lil Alamin.